Pendidikan Damai Berdimensi Sufistik: Alternatif Merajut Kebhinekaan Masyarakat Indonesia - Muvid, Muhamad Basyrul (Jurnal Penelitian Pendidikan Islam, 2022)
Peace education with a Sufistic dimension is one of the middle ways to strengthen and restore the dynamics of unity in the midst of pluralism. The purpose of writing this article is to critically conceptualize and reconstruct peace education with a Sufistic dimension. The research method uses library research by collecting various reference sources from books, journals and various documents on the theme. The findings conclude that first, peace education has a Sufistic dimension as an educational model that internalizes the values ​​of nobility, peace, ethics, love, compassion, and a sense of humanity. Second, the role of peace education with a Sufistic dimension is to form a community of people who love brotherhood, live in harmony, and are strong in terms of social solidarity. Third, the contribution of peace education with a Sufistic dimension is to maintain social political and religious stability of the community, directing the moderate paradigm and strengthening social human values, then the challenge is the movement of radicalism, hoaxes, fanaticism, egoism, intolerance and lack of deep understanding of religion.